Main Methods of Reconstruction of the Tourism System of Historical City Centers - Khurramovich, Kahhorov Azimjon (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, the preservation and rational use of architectural, historical and cultural monuments; reconstruction of ancient ones and beautification of new cities; transport, road construction; utilities; local industry and trade - all of which analyzed the prospects for the development of tourism, the method of development of these areas of activity. As a result of these studies, recommendations were developed for the general methodology of urban reconstruction, the methodology of planning and reconstruction of historical city centers, the methodology of accounting for architectural monuments, the protection of historical and cultural monuments in historical cities, the preservation of planning structures of historical value.